Advanced composite materials in aircraft applications / Mohd. Nizam Mohd. Zain and Mohd. Nazirudin Tahir - Mohd. Zain, Mohd. Nizam; Tahir, Mohd. Nazirudin (2000)
The exciting thing about composites is that an ordinary person can make things that they have never been able to make before, such as bathtubs, a boat, or a motorcycle. Race car bodies, canoes, airplanes, model aircraft, jet skis, boats, sculpture, as well as traditional industrial molding and model making have taken on a new dimension as fiberglass becomes less of a mystery, easier to use, and easier to buy. The materials that are used are easiest to understand when you think about something like a boat. A boat is hard, it doesn't bend, and it certainly doesn't take in water. Most people think of a boat as being made of "fiberglass."